A STUDY ABOUT ENTERPRISE ARCHITECTURE CONCEPT UTILIZATION ON A PROGRAM STUDY CURRICULUM ARCHITECTURE - Iskandar , Michael
Education is one of the pillars that supports the continuation of human civilization. One of the main forms of education in modern society is the teaching process that occurs in educational institutions or schools, including institutions of higher education. The learning processes done by these educational institutions are nowadays carried out based on a plan that is commonly referred to as a curriculum. One of the criteria that a good curriculum must have is a good relation between the miscellaneous knowledge units within the curriculum, whereas the number of knowledge units that can be found in a curriculum is often very large and is distributed in various courses. This makes it difficult for the management of the higher education institution that is responsible for the academic field. They have to monitor it in such a way as to ensure that changes in one course are still on track with other courses as well as the educational objectives that have been stated by the institution. Based on this problem that the curriculum management faces, there appears to be a prospect to create a framework that can be used to map all the aspects of a curriculum. This framework will be a conceptual model of the curriculum architecture as it is used in institutions of higher education. The framework that is created is based on the enterprise architecture concept. The type of research done is design science research (DSR), which is a type of research where something new is created, something which did not exist previously. The first step of the research is the application of an analogy theory to prove that the enterprise architecture concept and the curriculum concept are analogous. With this done, any further effort to create a curriculum architecture framework based on an enterprise architecture can be accounted for. The effort of creating the curriculum architecture framework itself uses knowledge from three different domains: curriculum, enterprise architecture, and knowledge. Specifically, it uses the curriculum model created by Ralph W. Tyler, the Zachman Framework, knowledge mapping, and Blooms Taxonomy of Educational Objectives: Cognitive Domain. The resulting curriculum architecture framework is a matrix that consists of three rows and six columns. The three rows represent three particular viewpoints of those who are deemed the most active in the creation of a curriculum: the study program, the specialization group, and the course coordination meeting. The six columns represent the know-why, know-what, know-how, know-who, know-when and know-where of one particular curriculum. The resulting curriculum architecture framework is tested using a case study method. The case study object is the Information Systems specialization group of the Accountancy study program at the Economics Faculty of the Parahyangan Catholic University (Unpar), in Bandung. The conclusions of this case study are: that the curriculum architecture framework can definitely be applied in the real world; also that the curriculum architecture framework is able to support curriculum quality enhancing efforts, because it is a tool that can be used to plan, control, manage, and evaluate the curriculum in an institution of higher education. For example, it was discovered that applying the curriculum architecture framework forces the user to make systemic drawings of the curriculum, thus highlighting relational weaknesses that exist in said curriculum. Additionally, the application of this curriculum architecture framework has shown that the creation of an information system to support this framework shouldnt be too difficult; that among some columns in the framework there are very strong linkages, while other columns are very much standalone; and that there are some columns which turn out not to be important to the user so that even though they are prepared by the analyst, the user will ignore them. The two last discoveries, of the strong and weak relationships between columns, and of the irrelevant columns, are open issues that are returned to the field of enterprise architecture, awaiting another occasion in which these can be researched.